Strategi Guru Sejarah Kebudayaan Islam dalam Penanaman Gemar Membaca pada Siswa - Ratih Pebrianti; Ritonga, Asnil Aidah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research was conducted to comprehensively describe and delve into the strategies used by Islamic Education (SKI) teachers to foster a love of reading among students at MTs Al-Ikhlas Sait Buntu using a qualitative descriptive approach with a naturalistic technique. The results of the study revealed that SKI teachers employ several strategies to encourage students to develop a love of reading, such as repeated reading, memorization, and sharing experiences. In the repeated reading strategy, teachers engage students in taking turns to read, allowing other students to focus on the presented text. In the memorization strategy, students are included collectively to ensure that all students can participate effectively in the learning process, while the sharing experiences strategy involves teachers narrating real-life situations to enhance students' curiosity. This, in turn, motivates students to read and seek knowledge continuously. The contribution of this research lies in providing information about effective strategies to cultivate an interest in reading among students in secondary education. The novelty of this research lies in combining various learning strategies into a single activity, enabling students to experience more diverse forms of learning. The utilization of multiple creative teaching strategies can enhance students' enthusiasm for reading.